2021
DOI: 10.1177/17534666211037454
|View full text |Cite
|
Sign up to set email alerts
|

A new protocol for exercise testing in COPD; improved prediction algorithm for WMAX and validation of the endurance test in a placebo-controlled double bronchodilator study

Abstract: Background: Two new protocols have been developed for bicycle exercise testing in chronic obstructive pulmonary disease (COPD) with an individualized cardiopulmonary exercise test (ICPET) and subsequent customized endurance test (CET), which generate less interindividual spread in endurance time compared with the standard endurance test. Main objectives of this study were to improve the prediction algorithm for WMAX for the ICPET and validate the CET by examining treatment effects on exercise performance of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…By comparing LAMA/LABA against placebo, two studies estimated CWRCE after treatment (these studies were not designed to evaluate the change from baseline). In both studies a mean increase in exercise capacity was observed with LAMA/LABA versus placebo in COPD (55 s [95% CI: 20–90, p = 0.013] [ 26 ] y 113 s [95% CI: 6–220, p = 0.037] [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing LAMA/LABA against placebo, two studies estimated CWRCE after treatment (these studies were not designed to evaluate the change from baseline). In both studies a mean increase in exercise capacity was observed with LAMA/LABA versus placebo in COPD (55 s [95% CI: 20–90, p = 0.013] [ 26 ] y 113 s [95% CI: 6–220, p = 0.037] [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The search strategies yielded 1590 articles, of which 17, including 4,041 patients, met the inclusion criteria, 2964 of the patients were treated with the LAMA/LABA combination, 1901 treated with placebo, 1070 treated with LAMA and 755 treated with LABA (Fig. 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The reference search yielded no further articles.…”
Section: Resultsmentioning
confidence: 99%